In situ characterization of porous VPO catalysts with fibrous structure: Identifying the redox behavior and the stability of active sites - Berenguer-Betrián, Raúl; Fornells, Jaime; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás; Ford, Michael; Wachs, Israel E. (My University, 2016)
Two VPO materials with fibrillar morphology have been prepared by the aid of electrospinning technique. One is a VPO carbon-supported material (VCF200) with fibrous morphology and very high surface area that is stable under oxidizing conditions up to 350C. The other material is a bulk mixed VPO oxide (VPO500) with fibrous structure obtained after optimizing the calcination of the carbon support in VCF200. Despite it is a bulk oxide material, this material exhibits a high surface area (> 60 m2/g). The redox behavior of both samples was monitored by in situ Raman spectroscopy under oxidation/reduction cycles. For the dehydrated supported sample (VCF200), the pyrophosphate phase (VO)2P2O7 (Raman ~930 cm-1) is detected, which has been described as the active phase (see Figure (a) below). This phase is quite stable since it does not disappear upon subsequent oxidation/reduction cycles. Under reduction conditions at 125C, in consecutive cycles, additional Raman bands appear at ~1090 cm-1 that are characteristic of the αII-VOPO4 phase. On the other hand, the bulk phases show a reversible behavior under redox cycles (Figure (b)). Under reducing conditions, a Raman band appears at ~980 cm-1 (β-VPO phase), whereas under oxidation conditions some segregation to VOx oxides occurs. Nevertheless, this segregation is reversible and the β-VPO phase forms again under reducing conditions. Thus, these results demonstrate that the active VPO phases of these fibrous catalysts are quite stable, and that their structure is reversible under several redox cycles, which make them suitable as oxidation catalysts.
Keywords: Catalizadores; Electrospinning; VPO; Catalysts